Virtual reality infrastructure and its application to telerobotics - Kim, Y.-Y.; Ko, H.; Choe, B.-H. (1994)
In this paper, we introduce the telepresence concept to the telerobotics area using the surveillance rover in the hazardous environment. We implemented the rover on the virtual reality hardware and software infrastructure at the Korea Institute of Science and Technology (KIST). The rover is teleoperated by an operator. It consists of a mobile frame and a stereo camera mounted on a motion platform, which tracks the head motion of the operator. With this setup, the operator can view the surroundings of the rover as he maneuvers the rover with a sense of presence at the rover. ？ 1994.
Keywords: Computer hardware; Computer software; Degrees of freedom (mechanics); Mobile robots; Technological forecasting; User interfaces; Video cameras; Hazardous environment; Korea Institute of Science and Technology; Stereo camera; Surveillance rover; Telepresence concept; Virtual reality; Interactive computer graphics